Investigative Reasoning: rational analysis of criminal investigation according to Game Theory (Brazilian Journal of Police Sciences, 2023)
The criminal investigation is presented as a process for the discovery of possible crimes. Investigative action in Brazil is operated through the Judiciary Police, responsible for collecting evidence of criminal materiality and evidence of authorship, with investigative acts being presided over by the police chief. The figure of the criminal investigation manager, in addition to the responsibilities related to the leadership and leadership role occupied in the administrative structure of the investigative police, has the mission of conducting the investigative process with scientificity, rationality and strategy. The adoption of logic in the decision-making processes related to the lines of investigation (initial hypotheses) to be followed triggers the cadence of acts related to the collection of information about the practice of crime. The strategic look at the execution of diligences involves the perspective that the criminal investigation is a game of interests between actors (investigators, victims, witnesses, investigated). In this way, game theory presents itself to assist in the structuring of strategic thinking in criminal investigation, presenting tools that help the decision maker to reflect rationally and in a planned way. The structuring of scientific thinking in criminal investigation allied to the notion of the need for strategic planning are essential structures for the development of an efficient criminal investigation.
Keywords: Criminal investigation; investigative mindset; logical reasoning; abductive method; game theory